A review of the influential factors on the heritage shophouses’ architectural design and place identity of urban historic districts in Malaysia / Mohd Amirul Hakim Zamri, Roshida Abdul Majid and Mohd Hisyam Rasidi - Zamri, Mohd Amirul Hakim; Abdul Majid, Roshida; Mohd Hisyam Rasidi, Mohd Hisyam (2022)
Heritage shophouses are the main architectural heritage that significantly characterized the place identity of the urban historic district in Malaysia since the 17th century through their unique architectural design character. Unlike the modern building design that is seen as contextually isolated from the place identity of the urban historic district, the heritage shophouses design is considered successful in intertwining with the place identity due to its architectural identity that significantly responds to contextual factors. This paper aims to systematically review the factors that influence Malaysian heritage shophouse design that contributes to its architectural identity constitution through content analysis. This paper extracts scholars’ works on heritage shophouse architectural design features, heritage shophouse morpho-typologies, and the factors that influence the constitution and development of its architectural identity. Many heritage shophouse styles in Malaysia morphologically developed over time, which can be classified into the Early Heritage Shophouse styles, the Eclectic Heritage Shophouse styles, and the Non-Cultural Heritage Shophouse styles. Nevertheless, architecturally, all heritage shophouses are characterized through the articulation of the façade design elements, the interior design features including the spatial organization system, and the building construction materials which are mainly influenced by the tropical topographical climates and material sources as a basic architectural adaptation, the building development standards set by the colonial regimes for the urban and living issues solutions, the cultural assimilation through the architectural design features and programs, and the development of building construction and materials. The findings of this study could help the designer how to set a design consideration priority in developing their new architectural intervention design idea in the urban historic district to preserve its valuable historical character.